Study guides

☆☆

Q: What about 8y?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

4y + 8y = 12y 4y - 8y = -4y 4y x 8y = 32y2 4y/8y = 1/2

-2

Not sure which you mean, take your pick: (8y)3+27=(8y+3)((8y)2-3*(8y)+9)=(8y+3)(64y2-24y+9); or 8y3+27=(2y+3)(4y2-6y+9)

16y2-8y=0 8y(2y-1)=0

7 + 8y - 3y + 2 =7 + 2 + 8y - 3y = 9 + 8y - 3y = 9 + 5y

Related questions

If: -8y-7 = -8+8y Then: -7+8 = 8y+8y And: 16y = 1 So: y = 1/16

4y + 8y = 12y 4y - 8y = -4y 4y x 8y = 32y2 4y/8y = 1/2

8y-79 = -71

6y-8y = -2

8y = 23y

-2

Not sure which you mean, take your pick: (8y)3+27=(8y+3)((8y)2-3*(8y)+9)=(8y+3)(64y2-24y+9); or 8y3+27=(2y+3)(4y2-6y+9)

(8x-8y)/(8x+8y) = (x-y)/(x+y)Cancel down by 8; you have simplified the equation.

If you mean (9x-8y)(9x+8y) then it is 81x^2 minus 64y^2

16y2-8y=0 8y(2y-1)=0

2y+8y = 10y

-8x-8y=-64 -8y=8x-64 y=-x+8

People also asked